2012
DOI: 10.1128/jvi.06665-11
|View full text |Cite
|
Sign up to set email alerts
|

A Human Antibody Recognizing a Conserved Epitope of H5 Hemagglutinin Broadly Neutralizes Highly Pathogenic Avian Influenza H5N1 Viruses

Abstract: e Influenza A virus infection is a persistent threat to public health worldwide due to its ability to evade immune surveillance through rapid genetic drift and shift. Current vaccines against influenza A virus provide immunity to viral isolates that are similar to vaccine strains. High-affinity neutralizing antibodies against conserved epitopes could provide immunity to diverse influenza virus strains and protection against future pandemic viruses. In this study, by using a highly sensitive H5N1 pseudotypebase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 53 publications
2
74
0
Order By: Relevance
“…These Abs potently neutralize all clades and subclades of HPAI H5N1 viruses except subclade 7.2. Furthermore, they protect against lethal challenge of both homologous and heterologous H5N1 strains (26,27). More recently, we showed that 65C6 and 100F4 Abs also cross-neutralize newly emerging HPAI H5N6 and H5N8 reassortants.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…These Abs potently neutralize all clades and subclades of HPAI H5N1 viruses except subclade 7.2. Furthermore, they protect against lethal challenge of both homologous and heterologous H5N1 strains (26,27). More recently, we showed that 65C6 and 100F4 Abs also cross-neutralize newly emerging HPAI H5N6 and H5N8 reassortants.…”
mentioning
confidence: 78%
“…In addition, Abs against the globular head with different degrees of cross-reactivity have also been isolated (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Many of these Abs are virus strain specific and recognize epitopes located in the receptor binding site (RBS), but some Abs recognize conserved epitopes within or outside the RBS of diverse strains of different subtypes (17)(18)(19) or within a HA subtype (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The antibody repertoire against epitopes located in the head is more diverse than those Abs targeting epitopes in the stem (31).…”
mentioning
confidence: 99%
“…Significant abrogation of binding in western blot analysis was observed when WLLGNP was mutated to WRRGNP. Another human mAb, 100F4, neutralises multiple clades of H5N1 and binds outside the receptor binding subdomain of H5N1 HA [12,22]. Memory B cells from peripheral blood mononuclear cells of a patient who recovered from H5N1 infection were immortalised and culture supernatants were screened by HA pseudotype-based neutralisation assay.…”
Section: Generation Of Neutralising Mabs Binding To the Ve Subdomainmentioning
confidence: 99%
“…Broad domain mapping for independent panels of anti-influenza mAbs are described from yeast libraries displaying fulllength, precursor influenza HA (HA0) or the HA1 and HA2 subunits separately (113,114). After confirming binding and domain localization, sublibraries of mutant HA fragments were generated by error-prone PCR for fine epitope mapping.…”
Section: Anti-influenza Mab Discovery Involving Yeast Displaymentioning
confidence: 99%